Γ-Aminobutyric acid plays a key role in plant acclimation to a combination of high light and heat stress. Issue 4 (25th January 2022) - Balfagón, Damián; Gómez-Cadenas, Aurelio; Rambla, José L; Granell, Antonio; de Ollas, Carlos; Bassham, Diane C; Mittler, Ron; Zandalinas, Sara I
Abstract: Plants are frequently subjected to different combinations of abiotic stresses, such as high light (HL) intensity, and elevated temperatures. These environmental conditions pose a threat to agriculture production, affecting photosynthesis, and decreasing yield. Metabolic responses of plants, such as alterations in carbohydrates and amino acid fluxes, play a key role in the successful acclimation of plants to different abiotic stresses, directing resources toward stress responses, and suppressing growth. Here we show that the primary metabolic response of Arabidopsis ( Arabidopsis thaliana ) plants to HL or heat stress (HS) is different from that of plants subjected to a combination of HL and HS (HL+HS). We further demonstrate that the combined stress results in a unique metabolic response that includes increased accumulation of sugars and amino acids coupled with decreased levels of metabolites participating in the tricarboxylic acid cycle. Among the amino acids exclusively accumulated during HL+HS, we identified the nonproteinogenic amino acid γ-aminobutyric acid (GABA). Analysis of different mutants deficient in GABA biosynthesis (GLUTAMATE DESCARBOXYLASE 3 [ gad3 ]) as well as mutants impaired in autophagy (autophagy-related proteins 5 and 9 [ atg5 and atg9 ]), revealed that GABA plays a key role in the acclimation of plants to HL+HS, potentially by promoting autophagy. Taken together, our findings identify a role for GABA in regulating plant responses to combined stress. Abstract : The amino acid γ-aminobutyric acid orchestrates plant acclimation to a combination of high light and heat stress.